Diagnosis of Stage II Rheumatoid Arthritis through Functional Evaluation of Wrist and Hand among Adult Females - Sana Saleem; Maleeha Fuad; Samreen Sadiq; Hafiz Muhammad Asim (Pakistan Journal of Medicine and Dentistry, 2020)
Background: